Towards web-based management for rural farmer products in Ketengah (WeRules) - Abdul Rahman, Mohd Nordin; Ahmad, Fadhilah (2005)
Advances in Internet technologies and related software applications increasingly drive a large number of businesses.The infrastructures provided by these information and communication technologies (ICT) reduce much of the cost of business implementations such as marketing strategies, advertising, transactions processing and collaborative information sharing. Based on these benefits, to achieve a better performance of marketing strategies this paper introduces a new approach to manage rural farmer products in Ketengah Terengganu by using a practical model of web-based portal (WeRules).Currently, the farmers encounter major problems to market their products to outside boundaries of their locations.As they lack of the necessary knowledge on marketing strategies, farmers either have to sell their products in a limited market boundary or capacity. The propose model composed a set of on-line functions such as farmer-products registration, buyers registration, web portal administration, brochure services, catalogue services and link and transactional services.Furthermore, the architecture of the web portal will also be demonstrated.The models identified may improve the quality, speed and realization of digital marketing as well as management for farmer community agriculture products in Ketengah Jaya. Finally, the future works and conclusion will be discussed.